Sustainability Evaluation of Sheep and Goat Rearing in Southern Italy. A Life Cycle Cost/Benefit Assessment - Pollaro, Nausicaa; Santagata, Remo; Ulgiati, Sergio (Journal of Environmental Accounting and Management, 2026)
Sheep and goat farming represent a non-negligible share of the worldwide livestock productions. Ovine rearing, although knowing time periods of growth and descents, is today gaining more interest especially with regards of milk and dairy products. This is due to the rediscovery of the economic, social and environmental potential of this type of farming and its products. This work aims to analyze goat farming and its productions using the life cycle assessment (LCA) method. LCA makes it possible to evaluate and understand the environmental impacts of livestock farming and dairy processing throughout all the phases of their production. The purpose is to highlight and localize the opportunities for reducing the environmental impacts; compare similar products to each other; evaluate and compare the effects related to different environmental and resource management policies. Two zootechnical companies, located in the province of Salerno (Italy), are investigated. The production process analyzed is precisely that of goat cheese, specifically the “Cacioricotta Cilentana”, a very well-known kind of Italian cheese. The characteristics of goat breeding and the production of Cacioricotta Cilentana are examined in this study. The similarities and differences between the two companies have been highlighted, linked to the breeding, cheese making and sale phases of the finished product. Applying the LCA approach, the environmental impacts of the production process were analyzed and quantified, according to the ReCiPe Midpoint (H) method to derive impact indicators relating to the most significant impact categories (including climate change, human toxicity, acidification, depletion of fossil resources, depletion of water resources). The evaluation highlights the critical points of the process so as to be able to suggest improvement options.